2015
DOI: 10.1371/journal.pntd.0003984
|View full text |Cite
|
Sign up to set email alerts
|

Classification of Rhinoentomophthoromycosis into Atypical, Early, Intermediate, and Late Disease: A Proposal

Abstract: BackgroundRhinoentomophthoromycosis, or rhino-facial conidiobolomycosis, is a rare, grossly disfiguring disease due to an infection with entomophthoralean fungi. We report a case of rhinoentomophthoromycosis from Gabon and suggest a staging system, which provides information on the prognosis and duration of antifungal therapy.MethodsWe present a case of rhinoentomophthoromycosis including the histopathology, mycology, and course of disease. For the suggested staging system, all cases on confirmed rhinoentomoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(43 citation statements)
references
References 28 publications
1
42
0
Order By: Relevance
“…The disease occurs more frequently in males than in females. In some areas of Africa, the male-to-female ratio is close to 3:1, whereas all cases of the world together showed a ratio of 8:1, very close to data from previous reports (129,130). This trend of high infection rates in males may be related to occupational activities.…”
Section: Age and Occupational Distributions Of Human Entomophthoramycsupporting
confidence: 86%
See 2 more Smart Citations
“…The disease occurs more frequently in males than in females. In some areas of Africa, the male-to-female ratio is close to 3:1, whereas all cases of the world together showed a ratio of 8:1, very close to data from previous reports (129,130). This trend of high infection rates in males may be related to occupational activities.…”
Section: Age and Occupational Distributions Of Human Entomophthoramycsupporting
confidence: 86%
“…In addition, Choon et al (171) suggested that chronic lymphedema could also play a role in the facial deformity observed in extreme chronic cases of rhinoconidiobolomycosis (118,130). According to the CLFLCV hypothesis, long-standing lymphostasis could induce permanent tissue overgrowth, as in elephantiasis cases (130). Choon et al (171) indicated that in chronic cases, the immune response does not control fungal growth.…”
Section: Putative Mechanisms Of Disease and The Host-pathogen Relatiomentioning
confidence: 99%
See 1 more Smart Citation
“…Atypical mucocutaneous conidiobolomycosis, defined by Blumentrath et al [45] as either facial infection in a region other than the nose and maxillary sinus or infection of a nonfacial cutaneous site has also been reported.…”
Section: Disease Manifestations and Clinical Diagnosismentioning
confidence: 99%
“…1,3,15,16 Blumentrath et al proposed a treatment strategy according to stages of disease progression; based on these classifications, the current case would be considered intermediate due to the incubation period and vestibular skin involvement and a surgical approach would not be recommended. 17 However, the current patient had non-responsive bleeding and a blocked airway; as such, his quality of life immediately improved following surgical debridement.…”
Section: Discussionmentioning
confidence: 74%